MUSIC THERAPY IN EARLY INTERVENTION - A FAMILY PERSPECTIVE - Gutierrez-Jimenéz, Susana; Franco, Vitor (Advances in Social Sciences Research Journal, 2018)
Background Music Therapy (MT) in Early Intervention currently works with children with disabilities or at risk of developmental delays in a family-centered model. Within a family centered approach the way parents receive and understand all the intervention is crucial, but has not been properly considered. Objective This paper aims to identify the role and value of MT in the perspective and representations of parents that attended therapy sessions with their children in the context of an Early Intervention Program. Methods Grounded Theory methodology is used to analyze data collected through interviews with 7 mothers and fathers of children with severe disabilities. Results Results show the significant value families set on Music Therapy specific interventions to facilitate motor areas, social and interpersonal relationships and engagement with music and sounds. Three large categories show that families are able to understand MT in Early Intervention context: what is Music Therapy, what are its benefits, and the effects it has on early development. Conclusions Music Therapy can be applied in the practice of Early Intervention teams and is compatible with a family-centered programs. It has the capacity to provide an effective contribution to improve nonverbal communication in primary relationships, particularly in more severe disorders when communication is unconventional. This work also allows to broaden current concepts on the clinical practice of MT in Early Intervention, moving from a traditional clinical approach to a family-centered one.